Shape memory polymers : theory and application - Kalita, Hemjyoti (De Gruyter, 2018)
The basic principles and mechanism of shape memory polymers, classification of shape memory polymers, and related characterization techniques are illustrated. Furthermore, an overview of the broad spectrum of applications in various fields for shape memory polymer is presented. Special focus will be given to hyperbranched, blended, interpenetrating and bio-based shape memory polymers, as well as shape memory polymer nanocomposites.